Prevalence of common viral skin infections in beach volleyball athletes - Tertipi, N.; Kefala, V.; Papageorgiou, E.; Rallis, E. (viruses, 2020)
Viral skin infections often affect the sports community. The aim of this study was to assess the rates, location sites, and seasons of appearance of common viral cutaneous diseases in beach volleyball athletes in Greece. Five hundred and forty-nine beach volleyball athletes participated in this study. The average age was 28.4 years. The viral infections were herpes simplex (type 1), molluscum contagiosum and warts. The measured parameters included: gender, age, the season when athletes may be more susceptible to infections and the location of infection in the body. Practicing information such as the number of training years, number of weekly trainings, and average hours of daily training was also recorded. Incidence rates correlated in relation to age: (a) warts (p < 0.001), molluscum contagiosum (p < 0.001), and herpes simplex (p = 0.001); (b) years of training: warts (p < 0.001), molluscum contagiosum (p < 0.001), and herpes simplex (p = 0.004); (c) average hours of daily training: molluscum contagiosum (p = 0.006) and herpes simplex (p < 0.010). The skin is the largest organ, and the risk of infection should not be underestimated. Prevention, early detection, recognition, and treatment are related to health and athletic performance, but also to the risk of transmission.